A Hermeneutical Reading of Postcolonial Literature: Fusion of Horizons in E.M. Forster's A Passage to India and Tayeb Salih's Season of Migration to the North - Bouziane, Laila (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
Hans-Georg Gadamer has consistently advocated the idea of understanding as a form of “fusion of horizons” that implies the important and active role of each part of a cross-cultural encounter. This paper proposes philosophical hermeneutics as an alternative way of reading of postcolonial literature. E.M. Foster’s A Passage to India and Tayeb Salih’s Season of Migration to the North, are postcolonial literary examples of diversity and otherness which are analyzed in the light of the hermeneutical concept of “fusion of horizons”. These texts include a range of contexts and circumstances in which communication is challenged by the characters’ different cultural backgrounds, and understanding is only to be achieved through the process of “fusion” of horizons which helps rework prejudices in order to reach a clearer vision. In this context, the hermeneutical “fusion of horizons” represents an alternative to traditional ways of “knowing” and understanding.